IMPLEMENTASI PMRI DALAM MATERI SIFAT KOMUTATIF DAN ASSOSIATIF PADA BILANGAN BULAT UNTUK LEVEL SISWA SD/MI - Ekasatya Aldila Afriansyah (Mosharafa: Jurnal Pendidikan Matematika, 2012)
Abstract                Implementing PMRI in teaching process using a little sheet box and straw as a media for helping students in learning commutative and associative properties in integer numbers is the aim of this study. Design research is used as appropriate means to achieve the aim; conducted in three phases: preliminary design, teaching experiment (first and second cycle), and retrospective analysis. This study enables students to work with contextual situations within integer numbers properties; uses media tool (a straw and little sheet box). Pendidikan Matematika Realistik Indonesia (PMRI) underlies the design of the context and the activities. Sample of population is students from Madrasah Ibtidaiah Negeri 1 Palembang. This study involves fourth grade students, 3 students in first cycle and 36 students in second cycle (4 students were analyzed in detail). The result of this study could show that the activities could bring students’ learning from the contextual situation to more formal situation. The activities within this study have been succeed to be implemented in this school so that these activities could be used for the others.